2000
DOI: 10.1002/1096-8628(20010101)98:1<15::aid-ajmg1014>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of receiving aBRCA1/BRCA2 test result

Abstract: Mutation analysis for autosomal dominant hereditary breast/ovarian cancer genes (BRCA1/BRCA2) became an important technique for women at risk of carrying these mutations. Healthy female mutation carriers have a high lifetime risk for breast and/or ovarian cancer and may opt for frequent breast and ovary surveillance or prophylactic surgery (mastectomy and/or oophorectomy). Psychological distress was assessed in 78 healthy women at risk of having inherited a BRCA1/BRCA2 mutation opting for genetic testing and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
0
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(161 citation statements)
references
References 23 publications
11
138
0
12
Order By: Relevance
“…Previous studies on genetic testing for a BRCA1/2 mutation did not find substantial psychological morbidity among women initiating genetic testing or receiving a positive test result (Lerman et al, 1996(Lerman et al, , 1998Croyle et al, 1997;Lodder et al, 1999Lodder et al, , 2001Coyne et al, 2000;Schwartz et al, 2002), which is in agreement with the well-being levels in our study. The DA had no negative impact on a broad range of well-being outcomes, and did not deter women from receiving their test result, while it improved understanding of the treatment options and consequences.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies on genetic testing for a BRCA1/2 mutation did not find substantial psychological morbidity among women initiating genetic testing or receiving a positive test result (Lerman et al, 1996(Lerman et al, , 1998Croyle et al, 1997;Lodder et al, 1999Lodder et al, , 2001Coyne et al, 2000;Schwartz et al, 2002), which is in agreement with the well-being levels in our study. The DA had no negative impact on a broad range of well-being outcomes, and did not deter women from receiving their test result, while it improved understanding of the treatment options and consequences.…”
Section: Discussionsupporting
confidence: 92%
“…53 Other studies have not reported any change in psychological risk with positive test results. 32,33,40,[57][58][59][60][61][62] Nonetheless, women who test positive for BRCA1/BRCA2 are also often met with resistance, shock, and other negative emotions from family members. [63][64][65][66] Similarly studies of individuals undergoing HNPCC testing demonstrate that the individual experiences of both unaffected and affected carriers are varied, but the majority experience an overall decrease in anxiety and depression.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…The most robust predictor of future distress is distress at baseline. 32,49,[57][58][59]68,[74][75][76][77] Additional risk factors include prior psychiatric history of depression, 74 history of using psychotropic medications, 75 passive or avoidant coping styles, 51,75,[80][81][82] or inaccurate risk perception, [85][86][87] which put individuals at risk of experiencing distress throughout the process or many years after receiving their results. Other important risk factors for future distress include being the first member of the family to obtain genetic testing, 33 having children, 76 experiencing the death of a relative from hereditary cancer, 34,78 as well as experiencing unresolved loss 5 and complicated grief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'évaluation des effets psychologiques de la communication des résul-tats des tests génétiques pour les personnes non malades n 'ayant pas la mutation délétère familiale d'un des gènes BRCA1/2 montre une diminution du niveau de détresse générale (dépression/anxiété) et du niveau de détresse plus spécifiquement liée à la maladie dans les suites des résultats [17,18]. Lodder a souligné la présence de niveaux de dépression élevés pour les femmes n 'ayant pas de mutation et dont une soeur était positive pour cette même mutation [19]. Pour les personnes non malades porteuses d'une mutation délétère, une augmentation de ces s ymptômes était observée après le rendu des résultats avec retour vers des seuils plus faibles pendant le suivi au long cours [20].…”
Section: Demande De Tests Génétiquesunclassified